The use of factorial design for levulinic acid extraction via hollow fiber supported liquid membrane - Vikneswary, Rajendaren; Syed Mohd Saufi, Tuan Chik; Mior Ahmad Khushairi, Mohd Zahari (Elsevier B.V., 2024)
Supported liquid membrane (SLM) is an effective method to separate a high-demand levulinic acid (LA) from an aqueous or biomass hydrolysate solution. Several factors can influence the separation of LA using SLM. In this study, three hollow fiber (HF) SLM (HFSLM) operation parameters, such as carrier concentration (0.1–0.5 M tri-n-octylamine, (TOA), stripping concentration (0.25–0.75 M sodium hydroxide (NaOH), and feed concentration (10–30 g/L LA) was analyzed by using a 23 full factorial design (FFD). The results showed that all three factors significantly impact the extraction of LA. The order of contribution effects towards LA extraction was LA feed concentration > NaOH stripping concentration > TOA carrier concentration. The design proposed a valid condition of factors such as 0.5 M TOA, 0.75 M NaOH, and 10 g/L of LA with LA extraction of 69.6 ± 2.16 %. The result proved that FFD effectively improved the LA extraction in the HFSLM process by considering all the factors involved.